Co : CdS diluted magnetic semiconductor nanoparticles: radiation synthesis, dopant-defect complex formation, and unexpected magnetism - Bogle, Kashinath A.; Ghosh, Saurabh; Dhole, Sanjay D.; Bhoraskar, Vasant N.; Fu, Lian-feng; Chi, Miao-Fang; Browning, Nigel D.; Kundaliya, Darshan; Das, Gour P.; Ogale, Satishchandra B. (Chemistry of Materials, 2008)
Incorporating a dopant into a nanoparticle is a nontrivial proposition in view of the size dependent surface versus bulk energy considerations and the intrinsic proximity of the surface to the interior, which facilitates migration to the surface. If realized and controlled, however, it can open up new avenues to novel nanomaterials. Some previous studies have shown the dopability of nanosystems but only with specific surface functionalization. Here, we demonstrate the successful dopant incorporation via a new route of pulsed high energy electron induced synthesis. We choose a system Co:CdS (dilutely cobalt doped cadmium sulfide) in view of the well-known application-worthy properties of CdS and the potential possibility of its conversion to a diluted magnetic semiconductor of interest to spintronics. By using various techniques, we show that matrix incorporation and uniform distribution of cobalt are realized in US nanocrystals without the need for additional chemical or physical manipulation. Optical and photoluminescence properties also support dopant incorporation. Interestingly, although magnetism is realized, it is weak, and it decreases at higher cobalt concentration. First principle density functional calculations are performed to understand this counterintuitive behavior. These calculations suggest that the introduction of parent cation or anion vacancies lead to magnetic moment reduction, albeit marginally. However, with some Co impurity fraction in the octahedral interstitial site inside the wurtzite cage, the magnetic moment drops down drastically. This study reveals that defect states may have an interesting role in dopant stabilization in nanosystems, with interesting system dependent consequences for the properties.

Characterization of biocompatible NiCo2O4 nanoparticles for applications in hyperthermia and drug delivery - Kale, Sangeeta N.; Jadhav, Anil D.; Verma, Seema; Koppikar, Soumya J.; Kaul-Ghanekar, Ruchika; Dhole, Sanjay D.; Ogale, Satishchandra B. (Nanomedicine-Nanotechnology Biology and Medicine, 2012)
Monodispersed, superparamagnetic nickel cobaltite (NCO) nanoparticles were functionalized using mercaptopropionic acid (MPA). MPA conjugates with NCO forming a metal-carboxylate linkage, with the MPA-MPA interaction occurring via formation of disulfide bonds, leaving another carboxyl end free for additional conjugation. The cytotoxicity studies on NCO-MPA show cell viability of similar to 100% up to a dosage of 40 mu g/mL on SiHa, MCF7, and B16F10 cell lines, and on mouse primary fibroblasts. Time-dependent cell viability studies done for a duration of 72 hours showed the cell lines' viability up to 80% for dosages as high as 80 mu g/mL. Negligible leaching (<5 ppm) of ionic Co or Ni was noted into the delivery medium. Upon subjecting the NCO-MPA dispersion (0.1 mg/mL) to radiofrequency absorption, the nanoparticles were heated to 75 degrees C within 2 minutes, suggesting its promise as a magnetic hyperthermia agent. Furthermore, the amino acid lysine and the drug cephalexin were successfully adducted to the NCO system, suggesting its potential for drug delivery. From the Clinical Editor: NCO-MPA nanopartciles were found to be promising magnetic hyperthermia agents, suggesting potential future clinical applications. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Cytotoxicity; drug delivery; Magnetic hyperthermia; Magnetic nanoparticles

Synthesis, characterization and in vitro study of biocompatible cinnamaldehyde functionalized magnetite nanoparticles (CPGF Nps) for hyperthermia and drug delivery applications in breast cancer - Wani, Kirtee D.; Kadu, Brijesh S.; Mansara, Prakash; Gupta, Preeti; Deore, Avinash V.; Chikate, Rajeev C.; Poddar, Pankaj; Dhole, Sanjay D.; Kaul-Ghanekar, Ruchika (Plos One, 2014)
Cinnamaldehyde, the bioactive component of the spice cinnamon, and its derivatives have been shown to possess anticancer activity against various cancer cell lines. However, its hydrophobic nature invites attention for efficient drug delivery systems that would enhance the bioavailability of cinnamaldehyde without affecting its bioactivity. Here, we report the synthesis of stable aqueous suspension of cinnamaldehyde tagged Fe3O4 nanoparticles capped with glycine and pluronic polymer (CPGF NPs) for their potential application in drug delivery and hyperthermia in breast cancer. The monodispersed superparamagnetic NPs had an average particulate size of similar to 20 nm. TGA data revealed the drug payload of similar to 18%. Compared to the free cinnamaldehyde, CPGF NPs reduced the viability of breast cancer cell lines, MCF7 and MDAMB231, at lower doses of cinnamaldehyde suggesting its increased bioavailability and in turn its therapeutic efficacy in the cells. Interestingly, the NPs were non-toxic to the non-cancerous HEK293 and MCF10A cell lines compared to the free cinnamaldehyde. The novelty of CPGF nanoparticulate system was that it could induce cytotoxicity in both ER/PRpositive/Her2 negative (MCF7) and ER/PRnegative/Her2 negative (MDAMB231) breast cancer cells, the latter being insensitive to most of the chemotherapeutic drugs. The NPs decreased the growth of the breast cancer cells in a dose-dependent manner and altered their migration through reduction in MMP-2 expression. CPGF NPs also decreased the expression of VEGF, an important oncomarker of tumor angiogenesis. They induced apoptosis in breast cancer cells through loss of mitochondrial membrane potential and activation of caspase-3. Interestingly, upon exposure to the radiofrequency waves, the NPs heated up to 41.6 degrees C within 1 min, suggesting their promise as a magnetic hyperthermia agent. All these findings indicate that CPGF NPs prove to be potential nano-chemotherapeutic agents in breast cancer.

Reduction of graphene oxide by 100 MeV Au ion irradiation and its application as H2O2 sensor - Hareesh, K.; Joshi, R. P.; Shateesh, B.; Asokan, K.; Kanjilal, D.; Late, Dattatray J.; Dahiwale, S. S.; Bhoraskar, Vasant N.; Haram, Santosh K.; Dhole, Sanjay D. (Journal of Physics D-Applied Physics, 2015)
Graphene oxide (GO) synthesized from a modified Hummer's method was reduced (referred, rGO) by using 100 MeV Au ion species and its response to the sense H2O2 was investigated. The changes in the atomic composition and structural properties of rGO after irradiation were studied using x-ray diffraction, Fourier transform infrared spectroscopy and x-ray photoelectron spectroscopy. These results suggested that the removal of the oxygen-containing functional groups and the improvement of the electrochemical performance of reduced graphene oxide (rGO) after ion irradiation. Raman spectroscopic results revealed the increase in the disorder parameter (I-D/I-G) after Au ion irradiation and also the formation of a large number of small sp(2) domains due to the electronic energy loss of ion beam. The resultant rGO was investigated for H2O2 sensing using electrochemical techniques and it showed a good response.
Keywords: electronic energy loss; GO; ion beam irradiation; reduction